Mode-specificity of vibrationally coherent internal conversion in rhodopsin during the primary visual event. - Schnedermann, C; Liebel, M; Kukura, P (American Chemical Society, 2015)
Conical intersections play a crucial role in photochemical processes, but limited experimental information exists on the structural distortions that couple electronic with reactive nuclear motion. Using ultra-broadband and highly time-resolved optical spectroscopy, we follow the evolution of vibrational wavepackets after passage through a conical intersection during the primary visual event, the 11-cis to all-trans photoisomerization of the retinal chromophore in rhodopsin. Comparison of nuclear coherences generated under resonant and off-resonant impulsive excitation conclusively reveals coherent wavepacket motion in the bathorhodopsin photoproduct over the full vibrational manifold. We observe strongly enhanced coherences in low-frequency torsional degrees of freedom over the fingerprint region and almost complete suppression of some hydrogen wagging motion. Our ability to monitor the multidimensional evolution of nuclear wavepackets across multiple electronic states is a general means for studying the structural and dynamic origins of efficient photochemistry and provides critical experimental information for theoretical studies.